Apoptotic Bodies in the Pancreatic Tumor Cell Culture Media Enable Label‐Free Drug Sensitivity Assessment by Impedance Cytometry. Issue 8 (20th May 2021) - Honrado, Carlos; Adair, Sara J.; Moore, John H.; Salahi, Armita; Bauer, Todd W.; Swami, Nathan S.
Abstract: The ability to rapidly and sensitively predict drug response and toxicity using in vitro models of patient‐derived tumors is essential for assessing chemotherapy efficacy. Currently, drug sensitivity assessment for solid tumors relies on imaging adherent cells or by flow cytometry of cells lifted from drug‐treated cultures after fluorescent staining for apoptotic markers. Subcellular apoptotic bodies (ABs), including microvesicles that are secreted into the culture media under drug treatment can potentially serve as markers for drug sensitivity, without the need to lift cells under culture. However, their stratification to quantify cell disassembly is challenging due to their compositional diversity, with tailored labeling strategies currently needed for the recognition and cytometry of each AB type. It is shown that the high frequency impedance phase versus size distribution of ABs determined by high‐throughput single‐particle impedance cytometry of supernatants in the media of gemcitabine‐treated pancreatic tumor cultures exhibits phenotypic resemblance to lifted apoptotic cells and enables shape‐based stratification within distinct size ranges, which is not possible by flow cytometry. It is envisioned that this tool can be applied in conjunction with the appropriate pancreatic tumor microenvironment model to assess drug sensitivity and toxicity of patient‐derived tumors, without the need to lift cells from cultures. Abstract : Drug sensitivity of an in vitro gemcitabine‐treated pancreatic tumor model is assessed from supernatants in culture media for shape‐based quantification of secreted subcellular bodies within distinct size ranges using their high‐frequency impedance phase versus size distribution determined by impedance cytometry, which is not possible by flow cytometry.